The Importance of Business Owners in Assessing the Size of Precautionary Savings - Hurst, Erik; Lusardi, Annamaria; Kennickell, Arthur; Torralba, Francisco (The Review of Economics and Statistics, 2010)
Not properly accounting for differences between business owners and nonbusiness owners in studies of household wealth can lead to erroneous conclusions about the significance of different saving motives. Using data from the Panel Study of Income Dynamics from the 1980s and 1990s, we show that within samples of both business owners and non–business owners, the amount of precautionary savings with respect to labor income risk is modest and accounts for less than 10% of total household wealth. Previous large estimates of the size of precautionary balances resulted from pooling these two groups together. Such pooling is inappropriate given that business owners face higher labor risk and accumulate more wealth than non–business owners for reasons unrelated to precautionary motives.